Design of an adaptive CubeSat transmitter for achieving optimum Signal to Noise (SNR) - Jaswar, Fitri Dewi; Ahmad, Yasser Asrul; Abdul Rahman, Tharek; Hindia, Mhd Noor (Aerospace Society Malaysia, Universiti Putra Malaysia, 2017)
CubeSat technology has open opportunity to conduct a space related research at a relatively low cost. To maintain CubeSat mission at an affordable cost, CubeSat typically uses a simple communication system using UHF link with fixed transmit power and data rate. However, CubeSat in Low Earth Orbit (LEO) does not have a relative motion with the earth rotation, resulting in a variable of the propagation path of the transmission signal. A transmitter with the adaptive capability to select multiple sets of data rate and RF transmit power are proposed to the improve the link optimization problem due to the variability of the propagation path. This paper presents the adaptive UHF transmitter design as a solution to overcome the variable of the propagation path. The transmitter output power will be adjustable from 0.5W to 2W according to the mode of operations and satellite power limitations. The transmitter is designed to have four selectable modes of operation to achieve optimum SNR and efficient power consumption based on link budget analysis and CONOPS requirement. Three prototypes were developed and tested for space-environment conditions such as radiation, vibration, and thermal vacuum test. Further detail about radiation test conducted at the Malaysia Nuclear Agency Laboratory is explained in this paper with the successful result for estimated more than seven months in the orbit exposure. Based on author knowledge, this radiation test using gamma source with 1.5krad exposure was the first conducted for satellite programmed in Malaysia.